(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
The multilingual documentation system of the United Nations represents a highly complex environment in which specialized concepts are simultaneously expressed through several linguistic systems. This creates a significant terminological problem, since lexical similarity between corresponding language units does not always ensure conceptual or institutional equivalence. The present study examines cross-linguistic terminological alignment in a specialized parallel corpus of United Nations documents and focuses on the relationship between terminological equivalence, semantic variation, contextual realization and institutional standardization. The study adopts a corpus-based comparative approach in which parallel textual segments are examined in order to determine how identical institutional concepts are represented across different languages.